The Contribution of Payroll Taxation to Wage Inequality in France - Antoine Bozio; Thomas Breda; Malka Guillot (Institute of Labor Economics (IZA), 2020)
Over the 1967-2015 period, net wage inequality has decreased in France by 25%, in contrast to the significant increase experienced by most developed countries. Less well known is the fact that labor cost inequality has actually increased by 8% over the same period. We show that, (a) standard demand-side explanations for the rise in inequality apply in France when tested using measures of labor cost (as they should be); (b) reforms to payroll taxation, jointly with increases in the minimum wage, can explain a large part of the decrease in net wage inequality, in the context of increasing market inequality.
Keywords: I24; J24; J31; 330; wage inequality; labor cost; payroll tax; Social Security contributions; tax incidence